Efektifitas Arang Serbuk Gergaji Kayu terhadap Pengaruh Penurunan Kadar Logam Berat Cadmiun (Cd), Cod dan Bod pada Sampel Air Sungai - Azis, Siti Safira Nurul Maulia; Iryani, A. Sry (Universitas Batanghari Jambi, 2025)
This study aims to evaluate the effectiveness of activated carbon derived from sawdust waste, both unactivated and activated, in reducing extreme pH levels, high temperatures, and heavy metals (especially Pb and Cd) in wastewater. Sawdust was converted into charcoal through a carbonization process, then activated using ZnCl₂ solution to enhance its adsorption capacity. Adsorption tests were conducted with variations in adsorbent mass and environmental parameters such as pH and temperature. The results showed that sawdust-based activated carbon significantly reduced Cd concentration, particularly at the optimum mass of 150 mg. Activated carbon performed better compared to non-activated carbon. In addition to reducing heavy metals, the adsorption treatment effectively lowered COD values (from 134.3 mg/L to 67.94 mg/L) and BOD values (from 20.4 mg/L to 14.4 mg/L), demonstrating the adsorbent’s capability to absorb organic compounds. Activation increased surface area and pore volume, thereby making the adsorption process more efficient. Overall, this study concludes that activated carbon from sawdust waste, especially after activation, is a low-cost, effective, and environmentally friendly adsorbent alternative for treating wastewater contaminated with heavy metals and organic matter.